A numerical model for a wet air-side economiser. (December 2015) - Lowrey, S.; Sun, Z.
Highlights: We present a model for two phase flow in a plate heat exchanger. We include the effects of turbulence inducing ribs with our heat exchanger model. The model is tested with varied numbers of hot-side and cold-side ducts. The model is integrated with a dehumidifier model. The model is validated against experimental geared dehumidifier data. Abstract: Geared dehumidifiers operating at low indoor temperatures can experience condensation in the air-side economiser. In this paper we present a numerical air-side economiser model which accounts for condensation in the hot-side ducting. The economiser model has been integrated with an existing dehumidifier model and the overall model tested under two modes – economiser with smooth ducts and economiser ducts embossed with turbulence inducing ribs. Numerical results from the ribbed duct tests are compared with experimental test data and, in the absence of empirical transfer coefficients for wet, rib-roughened rectangular ducts, enhancement factors have been used to model rib effects. Model results are also presented for a varied number of hot-side economiser ducts and the numerical data show reasonable agreement with experimental data showing that the model is suitable for the design and analysis of geared dehumidifiers operating with plate type economisers.